Consumers' environmental and ethical consciousness and the use of the related food products information: The role of perceived consumer effectiveness. (1st December 2016) - Ghvanidze, Sophie; Velikova, Natalia; Dodd, Tim H.; Oldewage-Theron, Wilna
Abstract: Consumers can be important active contributors to a sustainable society by selecting food choices that are both healthy and produced respecting environmental and socially ethical standards. The current study investigates five consumer behavioural factors – namely, perceived consumer effectiveness (PCE); environmental conscious behaviour; concerns for ethical food production; health conscious lifestyle; and healthy dietary patterns. The key interest of the study lies in exploring the moderating role of PCE - the extent to which the consumer believes that his/her own efforts can make a difference - in these interrelationships. The empirical analysis was conducted through an online survey of food consumers implemented in three markets - the US, the UK and Germany. Findings indicate that for individuals with higher levels of PCE, who are environmental conscious and ethically concerned, information on food labels relating to environmental and social issues represents value by itself. Interestingly, health and nutrition information on food labels was not perceived valuable by consumers with high PCE. The predictive effects of various socio-demographic variables on PCE, consumer environmental and health consciousness are discussed. Cross-cultural differences are also outlined. The results of this research may contribute to the development of environmental policies and communication strategies of the food industry to enhance perceived consumer effectiveness among consumers. Improved PCE, in turn, may catalyze consumers' environmental behaviour and ethical concerns in relation to consumption of food products with environmental and social information.